Earthquake engineering in Britain proceedings of a conference organized by the Institution of Civil Engineers and the Society of Earthquake and Civil Engineering Dynamics, held at the University of East Anglia, 18-19 April 1985. (Thomas Telford, 1985)
Earthquake engineering in Britian is the focus of these papers. They investigate British earthquakes using the national monitoring network of the British Geological Survey, compare two historical earthquakes in North Wales, and look at seismic engineering requirements in British industry.